The weeks before 100 persecutory delusions: the presence of many potential contributory causal factors. Issue 5 (September 2019) - Freeman, Daniel; Morrison, Anthony; Bird, Jessica C.; Chadwick, Eleanor; Bold, Emily; Taylor, Kathryn M.; Diamond, Rowan; Collett, Nicola; Černis, Emma; Isham, Louise; Lister, Rachel; Kirkham, Miriam; et al.
Abstract : Background: The period before the formation of a persecutory delusion may provide causal insights. Patient accounts are invaluable in informing this understanding. Aims: To inform the understanding of delusion formation, we asked patients about the occurrence of potential causal factors – identified from a cognitive model – before delusion onset. Method: A total of 100 patients with persecutory delusions completed a checklist about their subjective experiences in the weeks before belief onset. The checklist included items concerning worry, images, low self-esteem, poor sleep, mood dysregulation, dissociation, manic-type symptoms, aberrant salience, hallucinations, substance use and stressors. Time to reach certainty in the delusion was also assessed. Results: Most commonly it took patients several months to reach delusion certainty ( n = 30), although other patients took a few weeks ( n = 24), years ( n = 21), knew instantly ( n = 17) or took a few days ( n = 6). The most frequent experiences occurring before delusion onset were: low self-confidence ( n = 84); excessive worry ( n = 80); not feeling like normal self ( n = 77); difficulties concentrating ( n = 77); going over problems again and again ( n = 75); being very negative about the self ( n = 75); images of bad things happening ( n = 75); and sleep problems ( n = 75). The average number of experiences occurring was high (mean 23.5, s.d. = 8.7). The experiences clustered into six main types, with patients reporting an average of 5.4 (s.d. = 1.0) different types. Conclusions: Patients report numerous different experiences in the period before full persecutory delusion onset that could be contributory causal factors, consistent with a complex multifactorial view of delusion occurrence. This study, however, relied on retrospective self-report and could not determine causality. Declaration of interest: None.